2017
DOI: 10.1186/s12199-017-0635-6
|View full text |Cite
|
Sign up to set email alerts
|

Effects of intrauterine exposures to polychlorinated biphenyls, methylmercury, and lead on birth weight in Japanese male and female newborns

Abstract: BackgroundThe effects of prenatal exposures to polychlorinated biphenyls (PCBs), methylmercury, and lead on birth weight remain disputable. The aim of this study was to investigate whether these chemicals affect birth weight of Japanese newborns, with special emphasis on determining whether these effects differ between males and females.MethodsThe subjects from Tohoku Study of Child Development, which was designed to examine the developmental effects of prenatal exposures to such hazardous chemicals, were 489 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
23
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 32 publications
(26 citation statements)
references
References 51 publications
2
23
0
Order By: Relevance
“…We previously reported that the psychomotor development in 18-month-old children of the coastal area was significantly correlated with cord-blood total mercury (THg) only in the boys, and that this association remained significant after adjustment for possible confounders, including maternal-plasma DHA and cord-plasma selenium [ 22 ]. This result suggests that boys are more vulnerable to methylmercury exposure than girls, which is consistent with a few other studies [ 22 , 23 , 25 , 26 , 27 ]; although most other studies on this subject did not include gender-specific analyses [ 28 ]. Even if the gender was considered, most birth cohort studies in children included it as a confounding variable, which needed to be controlled and generalized the chemotoxic effects without accounting for possible gender discrepancies [ 29 ].…”
Section: Introductionsupporting
confidence: 90%
See 1 more Smart Citation
“…We previously reported that the psychomotor development in 18-month-old children of the coastal area was significantly correlated with cord-blood total mercury (THg) only in the boys, and that this association remained significant after adjustment for possible confounders, including maternal-plasma DHA and cord-plasma selenium [ 22 ]. This result suggests that boys are more vulnerable to methylmercury exposure than girls, which is consistent with a few other studies [ 22 , 23 , 25 , 26 , 27 ]; although most other studies on this subject did not include gender-specific analyses [ 28 ]. Even if the gender was considered, most birth cohort studies in children included it as a confounding variable, which needed to be controlled and generalized the chemotoxic effects without accounting for possible gender discrepancies [ 29 ].…”
Section: Introductionsupporting
confidence: 90%
“…TSCD is a prospective birth cohort study that investigates the effects of neurotoxicants on child development in Japan with the objective to determine the potential risks and benefits of seafood eating during pregnancy. TSCD consists of two birth cohorts, an urban area and a coastal area cohort, in northeastern Japan [ 19 , 20 , 21 , 22 , 23 , 24 ]. The purpose of the urban area cohort is to examine the effect of PCB exposure, and that of the coastal area cohort is to examine the effect of prenatal methylmercury exposure on child development.…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, Llop et al (2012) showed that the coefficient between prenatal mercury exposure and psychomotor scale in girls was negative and almost reached statistical significance, when this analysis was conducted for all subjects including boys and girls. According to previous research on methylmercury, the proportion of stillborn fetus due to prenatal exposure and the strength of associations with intrauterine growth seemed to be higher for males than for females (Foldspang and Hansen 1999;Sakamoto et al 2001;Tatsuta et al 2017). Taken together, these results suggest that psychomotor development of males is more likely to be affected by prenatal exposure to methylmercury than that of females.…”
Section: Discussionsupporting
confidence: 48%
“…This finding may suggest that male fetuses are more susceptible to methylmercury than female counterparts. In fact, there was a significant association of cord-blood mercury with low birth weight in male newborns, but not in females (Tatsuta et al 2017). Likewise, two studies found the adverse effect of methylmercury on the PDI only in male infants (Davidson et al 1995;Marques et al 2015); however, another study observed it only in female infants (Llop et al 2012).…”
Section: Introductionmentioning
confidence: 90%
“…Although the reason for this sex-specific difference is unclear, no statistically significant difference was observed in cord serum between male and female offspring regarding the concentration of mercury. Prenatal exposure to mercury affects neonate behavioural ability and birth weight in males, but no apparent effect was previously observed in females 6,43 ; moreover, a decrease in male, but not female, birth rate caused by Minamata disease was also observed. 3 It has been reported that male foetuses/infants are more sensitive to mercury exposure than females during development.…”
Section: Discussionmentioning
confidence: 73%